Net Neutrality in the Content Provision and Internet Service Provision Markets - Turgut Erkul; Sencer Ecer (İstanbul İktisat Dergisi)
Relaxing net neutrality in the form of introducing termination fees and its welfare effects are considered in a model of imperfect complements. The equilibrium of the game between the internet service provider (ISP) and the content provider (CP) yields welfare-maximizing termination fees that depend on the relative size of the ISP’s and the CP’s own-price effects and the cross-price effects. Only when the ISP’s own price effect is relatively high compared to that of the CP’s, along with high cross price effects, such a fee should be allowed. On the other hand, when the CP’s own price effect is relatively high compared to that of the ISP’s, along with high cross price effects, mergers are expected and are likely not harmful to social welfare. Telecommunication regulators may find the results useful in their net neutrality decisions.